Analisis Kemampuan Literasi Informasi Mahasiswa Ilmu Perpustakaan Uinsu Terhadap Pencarian Informasi - Nurmala Lubis; Franindya Purwaningtyas; Rahma Sariva Asdi; Zaki Fahri3; Rahmat Al-Rasyid Saragih (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine the interests and abilities of UINSU students in finding information in the UINSU library, to determine the literacy level of UINSU students, to determine the level of ability of UINSU students to search for information in the UINSU library, to determine the motivating factors of UINSU students in seeking information at UINSU. UNISU library. This study uses a descriptive research type, which means a systematic, factual, and accurate description of the facts, characteristics and relationships between the phenomena being investigated. Research that uses descriptive type is research that is intended to describe, describe, or explain the state of the object being studied as it is about how to find out how the information literacy skills of UINSU students are in finding information. This research results that UINSU Library Science students have a high literacy level and of course this is reflected in the information literacy that has been applied in information retrieval. And, in searching for this information, Library Science Students have used information media, Keywords: Information Literacy, Library, Information Search